Analytical solution for laser evaporative heating process: time exponentially decaying pulse case - Kalyon, M.; Yilbas, B S. (IOP Publishing, 2001)
The modelling of the laser heating process gives insight into the laser workpiece interaction and minimizes the experimental cost. In the present study, analytical solution for the laser pulse heating process is considered and the closed form solution for the temperature rise due to time exponentially varying pulse is obtained. In the analysis, evaporation of the surface is taken into account. A Laplace transformation method was used when formulating the closed form solution for the temperature profiles. The effect of pulse parameters on the temperature profiles is examined in detail. It is found that the closed form solution derived from the present study reduces to the previously obtained analytical solution when the surface recession velocity is set to zero in the closed form solution. Moreover, the predictions of numerical simulation and closed form solution are found to be in good agreement.